The audience and its theater: notes in form of an essay - Kinas, Fernando [UNESP] (Univ Sao Paulo, Escola Comunicacoes & Artes, 2017)
Analysis of the relations between the scene and the public in modern and contemporary theatrical phenomena, with the defense of a socio-aesthetic approach to actor-spectator relations in the historical, aesthetic and political contexts in which they are produced.
Keywords: Actor-spectator; Modern theatre; Contemporary theatre; Socio-aesthetic analysis